Model Perwujudan Good Faith (Asas Itikad Baik) Dalam Pemberantasan Mafia Tanah Terhadap Peralihan dan Pendaftaran Hak Atas Tanah Di Indonesia: A Model for the Realisation of Good Faith in the Eradication of the Land Mafia on the Transfer and Registration of Land Rights in Indonesia - Laila, Fathul (WARKAT, 2023)
Land actually provides a peaceful place where humans are born, live their lives, until they die and are buried together with nature, but land can have a winding history with all the tragic dramas and euphoria including the drama of land seizures both among individual communities and forced seizures by the State in terms of stripping property rights, land expropriation or land dispossession, as well as forced seizures, namely unilateral recognition of land, land appropriation where all become life dramas that flow blood and tears. The purpose of this research is to analyze the model of the realization of good faith in the eradication of the land mafia against the transfer and registration of land rights in Indonesia. The model of handling crimes in the land sector, especially related to the rise of the land mafia, can be done preventively and repressively in which the handling requires cooperation with various parties including the Police (Anti Land Mafia Task Force), the Attorney General's Office, the Supreme Court, the Judicial Commission, and others. It takes a deep awareness and a noble inner attitude and must always be held firmly by all stake holders as an effort to create a high moral attitude, avoid despicable acts, uphold the values of honesty, truth, and justice in order to realize the guarantee of legal certainty that is fair to land rights throughout the territory of the Republic of Indonesia so that the essence of good faith in the transfer and registration of land rights is interpreted as providing protection for the values to be maintained by the laws and regulations in contractual relations due to the legal act of transferring rights / transferring land rights before PPAT.